2016
DOI: 10.1021/acs.cgd.5b01717
|View full text |Cite
|
Sign up to set email alerts
|

P–N Junctions in Ultrathin Topological Insulator Sb2Te3/Bi2Te3 Heterostructures Grown by Molecular Beam Epitaxy

Abstract: We fabricated topological insulating Sb2Te3/Bi2Te3 p–n heterostructures by means of molecular beam epitaxy and characterized the topography of the films by scanning tunneling microscopy. Due to the van der Waals growth mode of the layered Te compounds, X-ray diffraction measurements show that the heterostructure is fully relaxed on the Si(111) substrate. Furthermore, scanning transmission electron microscopy measurements unveil the crystalline structure of the p–n interface. Energy dispersive X-ray spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 21 publications
2
37
0
Order By: Relevance
“…ARPES data revealed that Dirac cone surface states still exist at the surface of Sb2Te3. Another group also reported Sb2Te3/Bi2Te3 heterostructures grown on Si(111) [125]. They found that ternary compounds formed at the interfaces due to Sb/Bi diffusion between layers.…”
Section: Heterostructures and Superlatticesmentioning
confidence: 98%
See 1 more Smart Citation
“…ARPES data revealed that Dirac cone surface states still exist at the surface of Sb2Te3. Another group also reported Sb2Te3/Bi2Te3 heterostructures grown on Si(111) [125]. They found that ternary compounds formed at the interfaces due to Sb/Bi diffusion between layers.…”
Section: Heterostructures and Superlatticesmentioning
confidence: 98%
“…In addition to growing ternary alloys, topological insulator p-n junctions have also been grown, typically using the binary compounds [125]. They found that ternary compounds formed at the interfaces due to Sb/Bi diffusion between layers.…”
Section: Heterostructures and Superlatticesmentioning
confidence: 99%
“…This passivation layer is formed during the initial stages of deposition followed by the emergence of a vdW gap bridge from the passivation layer to the rst Te layer of the growing GST thin lm. 78,112,113 Consequently, only weak interactions between the substrate and thin lm are present enabling almost strain-free epitaxy. The strain energy between the substrate and thin lm is released rst by introduction of mist dislocation into the passivation layer and second by slight in-plane rotation of GST grains due to domainmatched epitaxy (Fig.…”
Section: Epitaxial Phase Change Thin Lms With Different Vacancy Strumentioning
confidence: 99%
“…Even more suited than ferromagnetic insulators, however, are other MTIs with higher transition temperatures, such as Cr doped Sb 2 Te 3 , with TC 's of 125 K for x = 0.42 and 190 K for x = 0.59, which is approximately linearly increasing with Cr doping . This combination of TIs in the form of Bi 2 Te 3 /Sb 2 Te 3 heterostructures preserves the TSS and simplifies the growth greatly due to the similar structural properties, effectively generating a hybrid TI system with higher order temperature and high magnetic moments …”
Section: Proximity Coupling and Heterostructuresmentioning
confidence: 99%